INDUSTRY-BASED LEARNING AS A PEDAGOGICAL BRIDGE: EFL LECTURERS’ VIEWS ON ESP FOR SUSTAINABLE HOSPITALITY - Faradillah Saputri; Ratnah Ratnah; Umar Iskandar (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This study explores English as a Foreign Language (EFL) lecturers’ perception of the relevance of Industry-Based Learning (IBL) in teaching English for Specific Purposes (ESP) within the sustainable hospitality context. The background of this inquiry lies in the need to ensure that English instruction in tourism polytechnics not only delivers theoretical knowledge but also equips students with practical communicative competence required in professional hospitality settings. Employing a qualitative approach, semi-structured interviews were conducted with six informants, including five EFL lecturers from Makassar and Lombok Tourism Polytechnics and one hospitality industry representative. Thematic analysis was applied to identify recurring themes and patterns across the data. Findings reveal that EFL lecturers consistently perceive IBL as a highly relevant and effective pedagogical model for ESP. They emphasized that IBL bridges the gap between classroom-based instruction and authentic workplace communication, providing students with opportunities to internalize language use through real tasks such as interacting with international guests, writing reservation emails, and producing promotional content. Lecturers also highlighted that IBL enhances students’ motivation, confidence, and professional attitudes, which are essential for employability in the global hospitality industry. Importantly, the integration of sustainability-oriented tasks—such as explaining eco-friendly hotel policies—further strengthens the contextual relevance of ESP instruction by aligning linguistic learning with industry transformation. This research concludes that IBL holds significant relevance for ESP in sustainable hospitality, not only for improving linguistic competence but also for nurturing professional readiness and sustainability awareness. The findings contribute to theoretical discussions on experiential learning and task-based pedagogy, while offering practical insights for curriculum design in hospitality education.